Biometric validation of a virtual reality-based psychomotor test for motor skill training. Issue 4 (1st October 2016) - Zhang, Wenjuan; Ma, Wenqi; Brandao, Maicom; Kaber, David B.; Bloomfield, Peter; Swangnetr, Manida
ABSTRACT: Psychomotor tests have been applied in clinical therapy and laboratory research as tools for evaluating motor and cognitive skills. Some studies have developed computerized versions of such tests using virtual reality (VR) systems with haptic interface controls. These systems allow for increased flexibility in test delivery and accuracy in performance assessment. In this study, a VR-based computer simulation of the block design (BD) test (a standardized psychomotor task as part of an adult IQ test) was developed and compared with the physical version of the test. Performance was evaluated based on four types of muscle activation collected using electromyography (EMG), time spent in completing the task, and subjective ratings of workload. Results verified the VR-based task as physically comparable to the conventional BD test. The validated computerized psychomotor task may be applied for both experimental and clinical use in future studies.